Hypofractionated radiotherapy of patients with glioblastoma: the first experience in Ukraine and prospects view - Gryazov, Andrey B.; Glavatskyi, Oleksandr Y.; Chuvashova, Olga Y.; Zemskova, Oksana V.; Andriichenko, Olena G.; Kruchok, Iryna V.; Griazov, Andrii A.; Spasichenko, Igor P.; Khmelnytskyi, Hennadii V.; Shuba, Iryna M.; Stuley, Volodymyr A. (Ukrainian Neurosurgical Journal, 2023)
Objective: To assess the survival of patients (pts) with newly diagnosed glioblastoma (GBM) in groups with hypofractionated regime radiotherapy, standard fractionationated regime radiotherapy and whole brain irradiation. Materials and methods: A retrospective non-randomized single-center study of 205 pts with GBM grade 4 according to the WHO classification treated in Romodanov Neurosurgery Institute named after Acad. A.P. Romodanov National Academy of Medical Science of Ukraine (2014–2020). The mean age of pts 53.8 years (95% CI 52.1 - 55.5); there were 114 men (55.6%) and 91 women (44.4%). According to the regimen radiotherapy (RT), pts were divided into 3 groups: 49 (23.9%) pts (standard RT: 2.0 Gy per fraction in 30 fractions, total dose 60.0 Gy) – group "sRT", 110 (53.7%) pts (hypofractionated RT: 3.5 Gy per fraction in 15 fractions, total dose 52, 5 Gy) - group "hRT", 46 (22.4%) pts – group "WBRT" (whole brain radiation). Differences in progression-free survival (PFS) and overall survival (OS) between the three groups were analyzed using Kaplan–Meier survival curve, log-rank test and Pearson Chi-square test. Results: The median OS is 15,0 (95% CI 14,1 – 17,1), 16,5 (95% CI 14,1 – 18,8) and 8,7 (95% CІ 7,5 – 9,5) months for sRT, hRT and WBRT, respectively. There is a significant difference in OS for sRT and hRT compared to WBRT (p=0.00000), without difference in OS between sRT and hRT (p=0.06757). The median PFS in sRT and hRT does not differ significantly: sRT – 9.0 (95% CI 9.0 - 10.0) months; hRT – 9.0 (95% CI 8.0 - 10.0) months. The median OS for WBRT is 5.1 (95% CI 4.0 - 6.0) months. There is a significant difference in PFS for sRT and hRT compared to the WBRT (p=0.00000), without difference in PFS between sRT and hRT (p=0.43374). The risk of death for WBRT compared to sRT is 2.5 times higher (HR 2.5 [95% CI, 1.45 - 4.46)) and 3.5 times higher compared to the hRT group (HR 3.5 [95% CI, 2.09-5.88)). The risk of progression for WBRT is 2.8 times higher (HR 2.78 [95% CI, 1.63-4.74)) compared to sRT, and 3.1 times higher (HR 3.12 [95% CI, 1.91-5.10)) compared to hRT. The broad implementation of hRT into clinical practice is specific to all modern radiation oncology. This trend is currently underway due to the specific positive clinical effects of hRT, which are discussed in detail in our publication. Conclusions: Our study demonstrates comparable survival outcome between sRT and hRT groups. This is an argument in favor of the feasibility of using hRT as a part of multimodal GBM treatment in terms of oncological outcomes. Further studies are needed to identify specific stratification groups of GMB patients with the greatest survival and quality of life benefits due to hRT.